Integration of NFC technology on household appliances - Dimaliwat, Bianca Irene P. (Animo Repository, 2018)
The study focused on developing a system that would monitor the usage of appliances in dormitories. This appliance management system will allow dormitory owners and tenants to utilize and to check how much power each tenant consumes per appliance, as well as the overall power consumption. Not only will the tenant learn how much energy he/she has consumed but the owner will also know its equivalence in terms of money. It includes a pre-paid and post-paid payment system. The project focused on expanding the usage of near field communication in terms of establishing smart connections between the user and all the electrical appliances inside a dormitory. The group also used MyRio microcontrollers in handling the operations on the entire system where connectivity, sharing and measuring information, and computations are concerned. © 2018 Universiti Teknikal Malaysia Melaka. All rights reserved.